Anesthetic Management of Supraglottic Tumors Undergoing Direct Laryngoscopy - Ajie, Astrandaya; Listiarini, Dian Ayu; Alfaruq, Ahmad Umar (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Supraglottic tumors are a type of tumor in the larynx that often causes airway obstruction. Comorbidities such as pulmonary tuberculosis (TB) and malnutrition can threaten patient safety during surgery. Comprehensive special perioperative anesthetic management involving multidisciplinary procedures and good communication between anesthesiologists and surgeons is needed. The aim of this case report is to understand the anesthetic management of a patient with a supraglottic laryngeal tumor with comorbid pulmonary TB, atelectasis and malnutrition.Case: A 44-year-old man came to the ear, nose and throat (ENT) clinic with complaints of shortness of breath since the previous month accompanied by pain while swallowing. The patient had a history of smoking and pulmonary TB. Computed tomography (CT) revealed a supraglottic tumor that was suspected to be malignant. The patient was programmed to undergo direct laryngoscopy for tissue biopsy.Discussion: The patient was intubated with a size 5 nonkinking endotracheal tube (ET tube) on the inside, which was connected to a size 7 kinking ET tube on the outside because the glottis rima was narrowed because of a tumor in the supraglottis so that only a small ET tube could pass to secure the airway. In this patient, induction therapy was performed with propofol and opioids. Muscle relaxants are not given to maintain respiratory muscle tone, especially in patients with pulmonary TB and atelectasis, who require full function of the respiratory muscles due to impaired lung development.Conclusion: Special perioperative management is needed in patients with supraglottic tumors with comorbid pulmonary TB, atelectasis and malnutrition. Airway management and the drugs and anesthesia induction techniques chosen must be agents that have minimal side effects on the respiratory tract and maintain respiratory muscle tone.